Formulation and Evaluation of Feminine Hygiene Preparation from Lemongrass (Cymbopogon nardus) and Its Inhibitory Activity Against Candida albicans - Yosi Darmirani rani; Fitri Siska (Jurnal FARMASIMED (JFM), 2025)
Background: Fungal infections are a common health problem in tropical countries, including Indonesia, where the hot and humid climate favors the growth of pathogenic microorganisms. One of the fungi that frequently causes infections in women is Candida albicans, the main agent responsible for vaginal discharge. Synthetic antibacterial and antifungal compounds often cause side effects, adverse events, relatively high costs, and the risk of fungal resistance due to excessive use. This situation has encouraged people to return to natural ingredients (“back to nature”) as safer, more effective, and more economical alternatives. One plant with strong potential as a natural antifungal agent is citronella (Cymbopogon nardus). This plant is widely known as a cooking spice, massage oil ingredient, and traditional herbal remedy, and it is abundantly available in the Hutaginjang area, North Tapanuli Regency. Objective: This study aimed to formulate and evaluate a feminine hygiene preparation containing citronella extract and to test its antifungal activity against Candida albicans. Method: The research was conducted experimentally. Results: The results showed that all formulations met the physical property standards set by SNI, with viscosity ranging from 2000–50,000 cps and pH between 4.0–5.0, which is suitable for the vaginal area. Antifungal testing revealed that inhibition zones increased with higher extract concentrations—10%, 15%, and 20% extracts produced inhibition zones of 10.5 mm, 13.3 mm, and 17.1 mm, respectively. The 60% extract yielded a 22.5 mm inhibition zone (categorized as very strong), approaching that of the positive control ketoconazole (29.1 mm). Statistical analysis (Shapiro-Wilk, ANOVA, Tukey HSD, Duncan) indicated that the data were normal, homogeneous, and showed significant differences between treatments. Conclusion: It can be concluded that higher concentrations of citronella extract are more effective in inhibiting the growth of Candida albicans.